2019
DOI: 10.7554/elife.43017
|View full text |Cite
|
Sign up to set email alerts
|

MYOD1 functions as a clock amplifier as well as a critical co-factor for downstream circadian gene expression in muscle

Abstract: In the present study we show that the master myogenic regulatory factor, MYOD1, is a positive modulator of molecular clock amplitude and functions with the core clock factors for expression of clock-controlled genes in skeletal muscle. We demonstrate that MYOD1 directly regulates the expression and circadian amplitude of the positive core clock factor Bmal1. We identify a non-canonical E-box element in Bmal1 and demonstrate that is required for full MYOD1-responsiveness. Bimolecular fluorescence complementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 70 publications
2
52
0
Order By: Relevance
“…In this respect, our findings indicate also that skeletal muscle timeless contributes to longevity (Fig. 8), in line with previous studies that have defined an important role for the skeletal muscle clock in mice (Harfmann et al 2015(Harfmann et al , 2016Hodge et al 2015Hodge et al , 2019Schroder et al 2015;Ehlen et al 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this respect, our findings indicate also that skeletal muscle timeless contributes to longevity (Fig. 8), in line with previous studies that have defined an important role for the skeletal muscle clock in mice (Harfmann et al 2015(Harfmann et al , 2016Hodge et al 2015Hodge et al , 2019Schroder et al 2015;Ehlen et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In skeletal muscle, many genes involved in glucose and lipid metabolism are regulated in a circadian manner (Hodge et al 2015;Harfmann et al 2016;Dyar et al 2018;Perrin et al 2018). Moreover, the skeletal muscle circadian clock has important roles in systemic homeostasis (Harfmann et al 2015;Hodge et al 2015Hodge et al , 2019Schroder et al 2015), as demonstrated by the finding that disruption of circadian rhythms in muscle leads to derangement of systemic glucose homeostasis and altered sleep in mice (Harfmann et al 2016;Ehlen et al 2017).…”
mentioning
confidence: 99%
“…Both miR-7 and miR-1 regulate the mTOR-related cell response to nutrient availability. For instance, miR-1 was found to be directly upregulated by the myogenic differentiation 1 (MYOD1) gene [52], which is a transcription factor essential for skeletal muscle development and myocyte fusion [53] and also functions as a circadian modulator in the peripheral muscle clock [54]. Noteworthy, MYOD1 was also significantly upregulated in the AL-T0/AL-T2 contrast (Additional file 2: Table S2), a finding that agrees well with the observed upregulation of ssc-miR-1 (Table 1).…”
Section: Differentially Expressed and Dispersed Mirnas Are Related Wimentioning
confidence: 99%
“…Bmal1 promotes satellite cell proliferation and differentiation, and is required for muscle regeneration 11,12 , Rev-erbα acts as an inhibitor of these processes 13 . Third, Clock/Bmal1 binds the E-box in the core enhancer of MyoD in a circadian manner; MyoD then binds the Bmal1 enhancer and increases the amplitude of Bmal1 expression, forming a feed-forward loop in myogenesis 14,15 .…”
Section: Circadian Regulation Is Tightly Integrated Into the Genetic mentioning
confidence: 99%